Technology adoption by women-owned businesses in Canada - Huju Liu; Hassan Faryaar (Economic and Social Reports)
Technology adoption is essential for improving the growth, productivity and competitiveness of businesses. Previous research suggests that women-owned businesses may be less likely to adopt technologies because they are usually smaller, face more financial constraints, are less likely to access technology knowledge or training, and have different risk-taking preferences. This paper linked two cycles (2017 and 2019) of the Survey of Innovation and Business Strategy with the Canadian Employer-Employee Dynamics Database to study the use of advanced and emerging technologies by women- and men-owned businesses in Canada. The study found some evidence of differences in the use of certain technologies by women-owned businesses, compared with men-owned businesses. Women-owned businesses (12.3%) were less likely to use emerging technologies, such as artificial intelligence, than men-owned businesses (16.5%). However, there was no significant difference in the use of advanced technologies. A Blinder–Oaxaca decomposition showed that the difference in characteristics between women- and men-owned businesses explained about 31% of the overall difference in using emerging technologies. Certain characteristics such as the share of women employees, the average age of employees, business age and profitability played a role in explaining the overall differences.